2021
DOI: 10.1002/phar.2619
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of antiplatelet response to low‐dose cangrelor utilizing platelet function testing in neuroendovascular patients

Abstract: Study Objectives The optimal antiplatelet therapy for emergent neuroendovascular stenting is uncertain. Cangrelor is an intravenous P2Y12 inhibitor that is an attractive option due its favorable pharmacokinetic profile and ease of measurability but optimal dosing remains unclear. The primary objective of this study is to characterize the dose response of low dose cangrelor (<2 mcg/kg/min) with the utilization of platelet function testing (PFT). Design A retrospective review of all patients treated with cangrel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…It seems likely that low-dose administration, inferior to standard, may be sufficient to obtain an efficient antiplatelet effect. 16,26 Among the available literature, distinct strategies and cangrelor dosages have been reported. The influence of cangrelor dosage on ICH risk remains to be properly evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…It seems likely that low-dose administration, inferior to standard, may be sufficient to obtain an efficient antiplatelet effect. 16,26 Among the available literature, distinct strategies and cangrelor dosages have been reported. The influence of cangrelor dosage on ICH risk remains to be properly evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Ten studies were case series, while one study was a retrospective cohort. Five studies reported cangrelor use with stent-assisted coiling or flow-diverter stents ( 13–15 , 25 , 27 ), three reported using cangrelor with stent-retriever and/or aspiration ( 10 , 12 , 26 ), two reported using cangrelor with acute stenting ( 11 , 29 ) and one reported using it with stenting or bridging ( 28 ). The bolus cangrelor regimen in included studies ranged from 5 to 40 μg/kg, while the infusion rate ranged from 0.75 to 4 μg/kg/min.…”
Section: Resultsmentioning
confidence: 99%